Use Of Jacobs ESL Composition Profile to Evaluate University Students’ Writing - Hari Prasad Tiwari (ELT Worldwide: Journal of English Language Teaching, 2023)
A teacher should have an access to a reliable soring rubric in order to assess the ESL/ EFL (English as a Second Language/ English as a Foreign Language) students' writing abilities accurately. One of the most widely used tools for assessing writing skills of non-native speakers of English is Jacobs ESL Composition Profile which can help teachers tailor their instruction to better meet the needs of their students. The present study attempts to determine the internal consistency between teachers i.e. raters who use Jacob’s Scoring Rubric (SR) to evaluate students' essays, describe the level of students' writing performance as measured by the Jacob’s SR, and describe teachers' viewpoints while using the profile. The research utilizes descriptive quantitative research design. The participants consisted of two ESL/EFL teachers who have been teaching and testing writing at bachelor’s level for more than five years and 40 fourth year ESL/ EFL students studying at undergraduate level at Madhypaschim Multiple Campus, Nepalgunj Banke, Nepal. The researchers used judgmental sampling to select the participants of the study. The teachers were instructed to score 40 essays written by fourth-year students. The finding revealed High internal consistency (r = 0.86, α = 0.00 < 0.05) between TA and TB when assessing student essays using the Jacobs ESL Composition Profile. In addition, the Cronbach alpha analysis reveals a value of 0.918, which suggests a high degree of consistency. The writing performance of students was found to be in four categories:  very good (3.75 %), good (52.5 %), satisfactory (36.5 %)   and acceptable (7.5 %). The outcome of the research demonstrates that the Jacobs ESL Composition Profile remains reliable for essay scoring, even though proficiency and experience are necessary due to its comprehensive guidelines.